Perilaku Mekanik Model Castellated Beam Pada Struktur Girder Baja Pedestrian Bridge Dengan Metode Elemen Hingga: Mechanical Behavior Of Castellated Beam Model In Steel Girder Structure Of Pedestrian Bridge Using Finite Element Method - Taufik, Syahril; Yulistiawan (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Castellated Beam is an efficient steel structure innovation, but it has the potential for Local Buckling due to holes in the web. Formation of Castellated Beam profiles from Hot Rolled Section WF 350x175x11x7 profiles to CB 525x175x11x7. The study analyzed the behavior of Castellated Beam models with variations in hexagonal hole cutting angles, flat structure geometry, camber and hybrid configurations. Element method analysis up to ANSYS R2025 steel girder structure application modeled 3D Shell Element SHELL181. The Shell Model is more accurate in representing the Castellated Beam structural response and is more efficient and easy in the computational modeling process, more suitable for the analysis of the Castellated Beam structure. The results of the 52° cutting angle study resulted in maximum strength. Castellated Beam camber with stiffener increases the ultimate load by 88.78% and decreases deformation by 40.36%. Hybrid configuration by improving the quality of the top flange can increase the performance of the structure by 40.38% by lowering the maximum voltage by 10%. The addition of a diaphragm to a double hybrid Castellated Beam un-camber span of 12 m and a distance between girders of 2.65 m can reduce deformation by 33.41%. Hybrid Castellated Beam camber is optimal in improving the performance of the structure efficiently. An increase in structural strength is obtained with an increase in maximum load that results in a bending stress close to the melting stress of each Castellated Beam hybrid element of about 90%-95%.